Career Narratives of Women Professors in South Africa - De la Rey, Cheryl Merle (Department of Psychology, 2014)
The statistics on the gender profile of academics in South African universities show that women are concentrated at the lower levels of the hierarchy with very few women at the uppermost level of professorship. At the time that this study was conducted women comprised only eight percent of the total number of professors in South Africa. The central aim of the study was to tell the story behind these statistics on gender inequalities by examining the subjective experiences of women academics. Twenty-five women professors from a diversity of universities, academic disciplines, race groups and ages were interviewed for about two hours each. The general areas of questioning were: family background, educational history, trajectory of career development, professional experiences, and relation between personal life and professional life. All interviews were audio-taped and then transcribed. Using narrative analysis, the interview transcripts were then analysed. The processes of analysis and interpretation were informed by the theoretical underpinnings of the study, which was located within the ambit of feminist post-structuralism and social constructionism. Central to the conceptualisation of the study was the idea of self as constructed through narrative with narrative viewed as an inherently social process. Thus the analysis of the narratives moved between attention to the particular and the general examining how broader historical and social processes of stratification are given form in the narratives of self. The unfolding of the narratives of the 25 women professors illuminated complex articulations between the legacy of apartheid and processes of gender organisation both inside and outside the academy. Both gender and race were pointed to as salient factors in the subjective representations of academia, but neither of these manifested as unitary and fixed. Instead gender and race shifted in and out of focus along with other axes of difference such as age, relationship status, family status and career stage in shaping the narratives of self. There were multiple and shifting intersections. Consequently, there were no straightforward, continuous lines of commonality and difference. Constructions of gender were shown to shift within a complex matrix of relations relevant to academia in South Africa. Albeit complex and multidimensional, the significance of gender in shaping academic careers was confirmed. The gendered implications of performing as an academic pervaded the narratives in diverse ways at the level of both form and content. While all the narratives followed a progressive form, the analysis showed that the career lines of most participants did not follow the standard linear model of career. The frequency of regressive micro-narratives nested in the larger progressive narrative drew attention to late beginnings and interruptions to career development. The analysis gave visibility to the interconnectedness of subjective experiences of being multiply positioned as academics, women, mothers and wives. Tension, ambivalence and contradiction permeated the accounts of having to perform multiple tasks. There was a shared representation of academic life as a battle to be fought. Achieving success in moving up the academic hierarchy was constituted as involving varied shifts in self-construction such as a change from the naive self to the ambitious, competitive self. Self-management, loneliness and isolation were commonly noted as features of academic life. A shared sense of gender consciousness and solidarity was largely absent from the narratives. Feminism was claimed as self-relevant in very few narratives whereas in others it was positioned as a reference point from which the self could be distinguished. Juxtaposed against feminism was the discourse of women's issues, which was framed as less militant and more womanly. These representations of feminism were interpreted in relation to the fissures that mark the historical development of feminism in South Africa. In sum, the study succeeded in producing a complex account of the subjective experiences of women professors in South Africa, giving visibility to the diverse ways in which social processes of gender are given form at the level of self-narrative. The varied narratives of what it means to be a woman professor in South Africa in the late 1990s were seen to be shaped by past policies, as well as current practices and policies. Finally, noting the diversity in the narratives, the importance of theorising difference was affirmed, the need for a complex change agenda was signalled and the need for a scholarship that is comfortable with the notion that our analyses are always limited, in process and constantly in need of modification was noted.